An efficient, mild and selective Ullmann‐type N‐arylation of indoles catalysed by Pd immobilized on amidoxime‐functionalized mesoporous SBA‐15 as heterogeneous and recyclable nanocatalyst. (3rd February 2015) - Ghorbani‐Vaghei, Ramin; Hemmati, Saba; Hamelian, Mona; Veisi, Hojat
<x xml:space="preserve">Abstract</x> A wide range of N‐arylated indoles were selectively synthesized through intermolecular C(aryl)N bond formation from the corresponding aryl iodides and indoles through Ullmann‐type coupling reactions in the presence of a catalytic amount of Pd immobilized on amidoxime‐functionalized mesoporous SBA‐15 (SBA‐15/AO/Pd(0)) under mild reaction conditions. These cross‐coupled products were obtained in excellent yields under mild conditions at extremely low palladium loading (ca 0.3 mol%), and the heterogeneous catalyst can be readily recovered by simple filtration and reused seven times with loss in its activity. Copyright © 2015 John Wiley & Sons, Ltd.